Levels of markers of coagulation and fibrinolysis systems in patients with pulmonary tuberculosis with concomitant diabetes mellitus after COVID-19 - R. Yu. Abdullaev; O. G. Komissarova; V. A. Shorokhova (Acta Biomedica Scientifica, 2024)
Background. It is known that COVID-19 can be followed by a shift in the hemostatic system towards hypercoagulation, which is more pronounced in the presence of diabetes mellitus (DM). Tuberculosis process is often accompanied with hypercoagulation syndrome. Of great interest is the study of the state of hemostatic systems in patients with pulmonary tuberculosis (TB) with concomitant DM who have had COVID-19.The aim. To study the relationship between the state of the hemostatic and fibrinolysis systems and moderate and severe COVID-19 in patients with pulmonary tuberculosis and diabetes mellitus.Methods. 32 patients with TB and DM were divided into two groups. Group 1 included 16 patients with TB and DM who have previously had COVID-19 (TB-DM-COVID). Group 2 included 16 patients with TB and DM who did not have COVID-19 (TB-DM).Results. It was found that TB-DM-COVID patients were more likely to develop a hypercoagulable shift compared to TB-DM patients. This was evidenced by a more frequent shortening of such indicator as activated partial thromboplastin time (43.7 % and 25.0 % of cases, respectively; χ2 = 7.22; p = 0.01), an increase in fibrinogen levels (43.7 % and 25.0%, respectively; χ2 = 7.22; p = 0.01) and D-dimer (43.7 % and 18.7 %, respectively; χ2 = 14.74; p = 0.0001). These changes were closely associated with the systemic inflammatory response, as strong and positive correlations were found between fibrinogen and C-reactive protein levels (r = 0.420; p = 0.01), and erythrocyte sedimentation rate (r = 0.433; p = 0.01) in TB-DM-COVID patients.Conclusion. In patients with pulmonary tuberculosis and diabetes mellitus after moderate and severe COVID-19, compared to patients who have not had COV ID-19, a hypercoagulable shift associated with the development of more pronounced systemic inflammation develops more often.